Pengelolaan Limbah Medis Covid-19 Berdasarkan Undang-Undang 32 Tahun 2009 Tentang Perlindungan dan Pengelolaan Lingkungan Hidup - Nia Ramadhanty Purwanto; Syauqi Al Amin; Ainun Mardiyah; Yosia Retno Wahyuningtyas (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2020)
Indonesia is currently undergoing major changes caused by Covid-19. One of the big changes is the increase in medical waste. Article 1 number 1 of Government Regulation No. 101 of 2014 concerning Waste Management of Hazardous and Toxic Materials ("PP No. 101 Of 2014") Covid waste is included in hazardous and toxic materials or B3 because it can harm health even to human safety. In addition to damaging the environment of medical waste used to handle Covid is at great risk of transmitting coronavirus if not managed appropriately. Because of this, this paper aims to control the presence of B3 waste so as not to further spread the virus and damage the environment. The method used is literature studies. The objective can be obtained by managing medical waste by means of reduction, storage, collection, transportation, management, hoarding. Every party that produces B3 waste must manage their waste that is infectious with Covid-19. It is not recommended to be immediately disposed of and can be destroyed first by burning and placed in a special place of infectious waste. It must be done the right management by separating the according with the type of waste. For the parties who still violate existing regulations, can be sanctioned. So that the environment can be protected and break the chain of spread of Covid-19.